Modelling for the electrical conductivity of graphite-modified asphalt concrete based on micromechanics - Yi Yang; Canlong Wu (Građevinar)
This paper proposes a novel micromechanics theory to model the electrical conductivity of graphite-modified asphalt concrete. The constraint range of electrical conductivity was derived according to the Hashin–Shtrikman (H–S) method. Based on the self-consistent (SC) method and percolation theory, a modified self-consistent (MCS) method was used to develop the electrical conductivity model. The results predicted by the MSC model were compared with the test data by adjusting the aspect ratio and percolation exponent. We highlight this new theory and its application to graphite-modified asphalt concrete, and demonstrate that the predicted values are in close agreement with the test data.